Organization of the mouse macrophage C-type lectin (Mcl) gene and identification of a subgroup of related lectin molecules. - Balch, S; Greaves, D; Gordon, S; McKnight, A (2002)
A number of genes encoding C-type lectin molecules have been mapped to the natural killer gene complex (NKC) at the distal region of mouse chromosome 6 and to a syntenic region on human chromosome 12p12-p13. In addition to those receptors which regulate NK cell function, related structures expressed on other cells types have also been localized to this chromosomal region. Among these are a number of recently characterized genes, including macrophage C-type lectin (MCL), macrophage-inducible C-type lectin (Mincle), dendritic cell immunoreceptor (DCIR) and dendritic cell-associated lectin-2 (Dectin-2). The amino acid sequences comprising the single C-type lectin domains of MCL, Mincle, DCIR and Dectin-2 are shown here to be closely related to each other. These molecules show overall similarity to two groups of animal C-type lectins, groups II and V, which demonstrate type II transmembrane topology. In this study, sequence analysis suggests that MCL, Mincle, DCIR and Dectin-2 represent a subset of group II-related C-type lectins which may participate in analogous recognition events on macrophages and dendritic cells. The genomic organization of the MCL gene and the sequence of the promoter region, with putative regulatory elements, were determined from a mouse MCL genomic DNA clone and are described here in detail.